The effects of quercetin on microRNA and inflammatory gene expression in lipopolysaccharide-stimulated bovine neutrophils - Chuammitri P. (2017)
© Chuammitri, et al. Aim: To investigate gene expression of microRNA (miRNA) milieus (MIRLET7E, MIR17, MIR24-2, MIR146A, and MIR181C), inflammatory cytokine genes (interleukin 1ß [IL1B], IL6, CXCL8, and tumor necrosis factor [TNF] ), and the pathogen receptor toll-like receptor (TLR4) in bovine neutrophils under quercetin supplementation. Materials and Methods: Isolated bovine neutrophils were incubated with bacterial lipopolysaccharide under quercetin treatment or left untreated. Real-time polymerase chain reaction was performed to determine the expression of the miRNAs and messenger RNA (mRNA) transcripts in neutrophils. Results: Quercetin-treated neutrophils exhibited a remarkable suppression in MIR24-2, MIR146A, and MIR181C expression. Similarly, mRNA expression of IL1B, IL6, CXCL8, TLR4, and TNF genes noticeably declined in the quercetin group. Many proinflammatory genes (IL1B, IL6, and CXCL8) and the pathogen receptor TLR4 had a negative correlation with MIR146A and MIR181C as revealed by Pearson correlation. Conclusions: Interaction between cognate mRNAs and miRNAs under quercetin supplementation can be summarized as a positive or negative correlation. This finding may help understand the effects of quercetin either on miRNA or gene expression during inflammation, especially as a potentially applicable indicator in bovine mastitis.